Are you more than the sum of your parents' genes? Phenotypic plasticity in a clonal vertebrate and F1 hybrids of its parental species. (19th May 2020) - Makowicz, Amber M.; Travis, Joseph
Abstract: All known vertebrate clones have originated from hybridization events and some have produced distinct evolutionary lineages via hybrid speciation. Amazon mollies ( Poecilia formosa ) present an excellent study system to investigate how clonal species have adapted to heterogeneous environments because they are the product of a single hybridization event between male sailfin mollies ( Poecilia latipinna ) and female Atlantic mollies ( Poecilia mexicana ). Here, we ask whether the hybrid species differs from the combination of its parental species' genes in its plastic response to different environments. Using a three‐way factorial design, we exposed neonates produced by Amazon mollies and reciprocal F1 hybrid crosses to different thermal (24°C and 29°C) and salinity (0/2, 12, and 20 ppt) regimes. We measured various ontogenetic and life history characteristics across the life span of females. Our major results were as follows: (1) Reaction norms of growth and maturation to temperature and salinity are quite similar between the two hybrid crosses; (2) Amazon molly reaction norms were qualitatively different than the P. latipinna male and P. mexicana female (L×M) hybrids for the ontogenetic variables; (3) Amazon molly reaction norms in reproductive traits were also quite different from L×M hybrids; and (4) The reaction norms of net fertility were very different between Amazon mollies and L×M hybrids. We conclude that best locale for Amazon mollies is not the best locale for hybrids, which suggests that Amazon mollies are not just an unmodified mix of parental genes but instead have adapted to the variable environments in which they are found. Hybridization resulting in asexuality may represent an underappreciated mechanism of speciation because the unlikely events required to produce such hybrids rarely occur and is dependent upon the genetic distance between parental species.